(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This paper investigates how individual corporate governance mechanisms affect the efficiency of credit risk management in commercial banks. Departing from studies that treat credit risk solely as an outcome level, the paper defines risk management efficiency as the ability of a bank to convert its risk-governance resources into superior credit quality relative to a best-practice frontier. Governance mechanisms are decomposed into board-level, committee-level, executive-level, and disclosure-level components, and their marginal contribution to efficiency is assessed. A two-stage methodology combining frontier efficiency estimation with regression analysis is proposed and discussed in the context of the Uzbek banking sector.